Toward assessing the role of dietary fatty acids in lamb's neurological and cognitive development - Tajonar, Karen; Gonzalez-Ronquillo, Manuel; Relling, Alejandro; Nordquist, Rebecca E.; Nawroth, Christian; Vargas-Bello-Pérez, Einar (Frontiers in Veterinary Science, 2023)
Understanding and measuring sheep cognition and behavior can provide us with measures to safeguard the welfare of these animals in production systems. Optimal neurological and cognitive development of lambs is important to equip individuals with the ability to better cope with environmental stressors. However, this development can be affected by nutrition with a special role from long-chain fatty acid supply from the dam to the fetus or in lamb's early life. Neurological development in lambs takes place primarily during the first two trimesters of gestation. Through late fetal and early postnatal life, the lamb brain has a high level of cholesterol synthesis. This rate declines rapidly at weaning and remains low throughout adulthood. The main polyunsaturated fatty acids (PUFA) in the brain are ω-6 arachidonic acid and ω-3 docosahexaenoic acid (DHA), which are elements of plasma membranes' phospholipids in neuronal cells. DHA is essential for keeping membrane integrity and is vital for normal development of the central nervous system (CNS), and its insufficiency can damage cerebral functions and the development of cognitive capacities. In sheep, there is evidence that supplying PUFA during gestation or after birth may be beneficial to lamb productive performance and expression of species-specific behaviors. The objective of this perspective is to discuss concepts of ruminant behavior and nutrition and reflect on future research directions that could help to improve our knowledge on how dietary fatty acids (FA) relate to optimal neurological and cognitive development in sheep.